Captopril challenge test: an underutilized test in the diagnosis of primary aldosteronism - Sharmin Jahan; Jun Yang; Jinbo Hu; Qifu Li; Peter J Fuller (Endocrine Connections, 2024)
Primary aldosteronism (PA) is the most common cause of endocrine hypertension and is often underdiagnosed. This condition is associated with increased cardiovascular morbidity and mortality in comparison to age and blood pressure matched individuals with essential hypertension (EH). The diagnostic pathway for PA consists of three phases: screening, confirmatory testing, and subtyping. The lack of specificity in the screening step, which relies on the aldosterone to renin ratio, necessitates confirmatory testing. The Endocrine Society’s clinical practice guideline suggests four confirmatory tests, including the fludrocortisone suppression test (FST), saline suppression test (SST), captopril challenge test (CCT), and oral sodium loading test (SLT). There is no universally accepted choice of confirmatory test, with practices varying among centers. The SST and FST are commonly used, but they can be resource-intensive, carry risks such as volume overload or hypokalemia, and are contraindicated in severe/ uncontrolled HTN as well as in cardiac and renal impairment. In contrast, CCT is a safe and inexpensive alternative that can be performed in an outpatient setting and can be applied when other tests are contraindicated. Despite its simplicity and convenience, the variability in captopril dose, testing posture, and diagnostic threshold limit its widespread use. This narrative review evaluates the diagnostic accuracy of the CCT across different populations, addresses controversies in its usage, and proposes recommendations for its use in the diagnosis of PA. Furthermore, suggestions for future research aimed at promoting the wider utilization of the CCT as a simpler, safer, and more cost-effective diagnostic test are discussed.